PENGEMBANGAN STRATEGI READING GUIDE DALAM MENGOPERASIKAN SOFTWARE CORELDRAW BAGI SISWA DENGAN HAMBATAN PENDENGARAN - Luqmanul Hakim Muttaqin, Ganda Sumekar, Yosfan Azwandi (Jurnal Penelitian Pendidikan Khusus, 2013)
The research was background by the problems that researcher found in the special senior high school level (SMLB) in Padang. The use of this study is to teach students with Reading guide to operate software CorelDraw. Approache of the study was using research and development. The result of this study shows that Reading Guide has successfull in student’s learning to operate software CorelDraw. Suggestions in this study is teachers can use the Reading Guide in providing computer materials for students with hearing impairment.